Evaluación del efecto del tiempo de contacto y voltaje aplicado sobre la depuración final de afluentes acuosos residuales de una planta de tratamiento convencional por electrocoagulacion a micro-escala - Francisco Javier Roque Rodriguez (2018)
Partial depurated domestic wastewater and evacuated of conventional Treatment Plant in our city to be used as water source for irrigation of large areas of crop and animal drinking was purified by electrocoagulation (EC) using micro-scale in laboratory obtaining encouraging results of final decontamination. The initial levels of physical, chemical and microbiological contamination of raw samples were reduced significantly without reaching the Estandares Nacionales de Calida Ambiental of water Category III described in DS N° 002-2008-MINAM because progressive alkalinization and heating suffering the water samples during this treatment; however, it was demostrated that the application of the EC allows the significant reduction of the electrical conductivity, total dissolved solids, oxygen demand expressed as BOD5 and COD and the content in total coliforms and the significant increase of its potential redox commonly negative ( - ) to get positive areas ( + ) wich was highly desirable, when we aplied higher voltage (24 volts) and longer (30 minutes) so its effect was found to be directly proportional to the purification achieved contacted with this innovative technology.